2014
DOI: 10.1002/jor.22694
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β signaling regulates fibrotic expression and activity in carpal tunnel syndrome

Abstract: Fibrosis of the subsynovial connective tissue (SSCT) is a predominant feature of carpal tunnel syndrome (CTS). While the nature of CTS has been extensively studied, little is known about the etiology of this disease. We investigated SSCT tissue from patients with CTS and control subjects using fibrosis arrays and cell culture analysis. Two-fold changes in fibrotic gene expression were found in multiple genes from patient SSCT using fibrosis arrays. This data was confirmed via qRT-PCR on a subset of genes; coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
44
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 50 publications
4
44
0
Order By: Relevance
“…6,28,32 The SSCT fibrosis in CTS is also marked by decreased matrix metalloproteases expression, an observation that fits with the increased fibrosis found in this tissue and a lack of normal matrix remodeling. 28,32-34 …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…6,28,32 The SSCT fibrosis in CTS is also marked by decreased matrix metalloproteases expression, an observation that fits with the increased fibrosis found in this tissue and a lack of normal matrix remodeling. 28,32-34 …”
Section: Discussionsupporting
confidence: 58%
“…6,28,29 In addition, this SSCT fibrosis is marked by increased TGF-b receptors, 6,30 increased activation of canonical TGF-b second messenger Smads, 28,31 increased expression of downstream fibrotic mediators such as CTGF, 28,29 and increased production of collagen types I, III, and VI. 6,28,32 The SSCT fibrosis in CTS is also marked by decreased matrix metalloproteases expression, an observation that fits with the increased fibrosis found in this tissue and a lack of normal matrix remodeling. 28,[32][33][34] In this study, we explored the ability of fibrotic SSCT cells to contract a collagen gel matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we did not assess the fibrotic phenotype of our cells after passage. However, in a parallel project, we have shown that a fibrotic phenotype is maintained after up to five passages in the CTS‐derived cells. Future work will explore biological mechanisms of action evaluating differences in gene expression, matrix organization, and interaction with cells and matrix degradation.…”
Section: Discussionmentioning
confidence: 89%
“…The F18 patient also had an additional carpal tunnel syndrome, which has been shown to upregulate several proteins including actin-binding proteins,19 thus possibly explaining why we did not observe the change. However, for GDAP1 mutations, the results were individual-specific (F26) as other GDAP1 patients recruited in the extended cohort clearly exhibited the decrease in PFN2 and GAMT.…”
Section: Discussionmentioning
confidence: 79%